Accessibility of German agglomerations. An approach with non-physical connectivity - Michael Bentlage; Stefan Lüthi; Alain Thierstein (European Regional Science Association (ERSA), 2010)
The knowledge economy plays a key role in the spatial development of cities and towns. Options of flexible spatial organization of company locations have influenced business strategies and decision-making in choosing locations. This process establishes complex network economies in which knowledge-intensive firms are linked together in both physical and non-physical ways. Many international knowledge-intensive enterprises have already recognized the advantage of being located around airports and within the corridors between the airport and the city. The shift to the emerging network economy puts a special focus on large polycentric urban agglomerations as centres for efficient face-to-face information exchange. This paper argues that there is a strong theoretical interplay between network economies and agglomeration economies. On empirical grounds we bring together the location behaviour of knowledge-intensive firms with an accessibility analysis based on road, rail and air data. Strong correlations between the global connectivity of intra-firm networks and the accessibility pattern of the German space economy are assumed. We therefore first look at how multi-branch multi-location firms in the knowledge economy develop their intra-firm networks, calculating connectivity values on various spatial scales. Second, we compare these interlocking firm networks with the accessibility patterns of the German space economy. The analytical building blocks are 338 Functional Urban Areas in Germany, including adjacent agglomerations in Germanyís neighbouring countries. It is shown that non-physical connection depends on air-access when interaction with international locations is intensive. For Interaction within Germany road and rail seem to be the most important modes of access.
Keywords: 330; knowledge economy; Germany; interlocking firm networks; connectivity; accessibility